A centre of excellence for infrastructure project preparation and PPP to fight climate change. (2019) - Ahamer, Gilbert
This article describes the concept for a regional centre of excellence and advisory facility for project design, financing and public-private partnership (PPP), using Central Asia (CA) as an example. The key task is to support partner countries in developing their bankable climate-related and environmental infrastructure projects for funding through international financial institutions (IFIs) while complying with their social and environmental project quality criteria. For the success of a Virtual Knowledge Centre (VKC), the communication options are essential. Its main task is to create a social community.